2010
DOI: 10.1016/j.ijsolstr.2010.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing spherical indentation: Contact regimes and mechanical property extractions

Abstract: Postprint (published version

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 56 publications
(93 reference statements)
6
26
0
1
Order By: Relevance
“…They formulated an equation to relate the change in the average pressure as a function of the ratio of combined elastic modulus to the yield strength. Indentation of spherical metallic surfaces was performed by Alcalá and Esqué-de los [65]. They found that the change in average pressure with deformation was similar to previous observations, in the absence of hardening or pileup.…”
Section: Model Validation and Discussionsupporting
confidence: 71%
“…They formulated an equation to relate the change in the average pressure as a function of the ratio of combined elastic modulus to the yield strength. Indentation of spherical metallic surfaces was performed by Alcalá and Esqué-de los [65]. They found that the change in average pressure with deformation was similar to previous observations, in the absence of hardening or pileup.…”
Section: Model Validation and Discussionsupporting
confidence: 71%
“…Literature reports a value of around 2.8 for the indentation constraint factor defined as the ratio of hardness or mean pressure to uniaxial flow stress [1,3,5,24,[44][45][46][47][48][49][50][51][52]. These studies are primarily inspired by Tabor's initial experiments conducted on copper and steel for which he identified a ratio of 2.8.…”
Section: Relationships Between Indentation and Uniaxial Measurementsmentioning
confidence: 99%
“…Indentation tests are mainly carried out using sharp indenters, such as Berkovich or Vickers tips. Tests using a spherical tip have also been described in the literature, although they are less common [3,7,8]. This specific test, in contrast to sharp tip indentation, may be used to characterize the elasto-plastic transition as the contact stresses increase with penetration depth.…”
Section: Introductionmentioning
confidence: 99%